Imaging Nanoscale Inhomogeneities and Edge Delamination in As‐Grown MoS2 Using Tip‐Enhanced Photoluminescence. Issue 11 (25th September 2019) - Rodriguez, Alvaro; Verhagen, Tim; Kalbac, Martin; Vejpravova, Jana; Frank, Otakar
Abstract : Methods for nanoscale material characterization are in ever‐increasing demand, especially those that can provide a broader range of information at once. Near‐field techniques based on combinations of scanning probe microscopy (SPM) and Raman or photoluminescence (PL) spectroscopy (tip‐enhanced Raman spectroscopy [TERS] and/or tip‐enhanced photoluminescence [TEPL]) are, thanks to their capabilities and fast development, strong candidates for becoming widespread across the scientific community as SPM and Raman microscopy did only a decade or two ago. Herein, a gap‐less TEPL study is performed directly on as‐grown MoS2 monolayer samples without any pretreatment or transfer, i.e., without the utilization of plasmonic substrate. Thanks to a mapping resolution as low as a few tens of nanometers, homogeneous layer interiors from defective edge fronts in the grown monolayers can be distinguished. With the aid of additional high‐resolution SPM modes, like local surface potential and capacitance measurements, together with nanomechanical mapping, a combination of defects and a lack of substrate doping is suggested as being responsible for the observed PL behavior in the partially delaminated MoS2 layers. In contrast, mechanically exfoliated flakes show topography‐ and contamination‐related heterogeneities in the whole flake area. Abstract : Tip‐enhanced photoluminescence in the gap‐less mode is utilized to discern local (tens of nanometers) inhomogeneities in the optoelectronic properties of as‐grown MoS2 monolayers. The results are put in contrast to measurements on exfoliated MoS2 . Special consideration is given to the edges, where photoluminescence enhancement and shift are observed in the grown MoS2 and ascribed to the edge delamination.